Infusing Critical Thinking into English Coursebooks - Ilyas, Hamzah Puadi (University of Muhammadiyah Prof. DR. HAMKA, 2016)
Though critical thinking has been officially written as one of educational objectives in Indonesia as written in the Regulation of the Republic of Indonesia Number 17 Year 2010 Regarding Educational Management and Administration, it seems that schoolteachers in this country still do not understand what it is and do not realise the importance of critical thinking for students and professionals of this country. This might be because there is no clear conception of what kind of critical thinking needed in education in this country, or it may be because Indonesian schoolteachers do not really know how to encourage students’ critical thinking as they may be still confused with this concept as mentioned above. The latest 2013 curriculum, however, seems to have accommodated the infusion of critical thinking into school subjects, as can been seen in the adoption of Bloom’s taxonomy. This article therefore attempts to argue what critical thinking can contribute to Indonesian students and people as well as proposes reading activities based on Ilyas’ critical thinking framework. This framework is the result of synthesising, examining and evaluating critical thinking taxonomies, strategies, programmes and tests.